A rare sinonasal tumour with orbital manifestation: glomangiopericytoma - Yap, Hui Jean; Sachlin, Ida Sadja'ah; Khaw, Bee Lian (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Sinonasal glomangiopericytoma is a tumor showing similarities to a glomus tumour but is less aggressive and has a lower malignancy potential. It was initially reported by Stout and Murray in 1942. Our patient was a 19 years old lady who presented to us with unilateral epistaxis during her pregnancy. Further investigations including a nasopharyngeal biopsy showed signs of an aggressive behaving sinonasal glomangiopericytoma. She underwent left medial maxillectomy via lateral rhinotomy approach to achieve complete excision of the tumor. This was vital as past literatures suggest that incomplete excision of tumor is the most pertinent factor to tumor recurrence. Distant metastasis is rare. Complete excision with regular long term follow up is the treatment of choice. The role of chemo and radiotherapy remains controversial.